The Origins of American International Retailing: Tiffany of New York in London and Paris, 1837–1914. Issue 2 (29th June 2017) - Alexander, Nicholas; Doherty, Anne Marie
Abstract : This article considers the international retailing activities of Tiffany of New York between 1837 and 1914. Using data from the company archive alongside other sources, the findings indicate that five factors were determinants of sustainable international retailing: a centralized organizational structure, a stable ownership structure, existing international engagement, a strong brand identity, and a relevant international retail format. Placing Tiffany's activities in its wider commercial and consumer context, the findings illustrate the organizational changes and asset combination required to support the development of early international retail operations. The article contributes to theoretical understanding of the dynamics of retail internationalization.